ANALISIS BUTIR SOAL UJIAN AKHIR SEMESTER GENAP MATA PELAJARAN PEKERJAAN DASAR OTOMOTIF SMK NEGERI 1 NGLEGOK - Vania Rustiansavitri; Drs. Sukaswanto, M.Pd (Department of Automotive Engineering Education, Faculty of Engineering, Yogyakarta State University, 2026)
This study aimed to know the qualities of question items at the end of the even semester for the basic automotive work for class X TKRO at SMKN 1 Nglegok. This study is using descriptive method with quantitative approach, documentation technique for collecting data. Students of class X TKRO at SMKN 1 Nglegok was being the subjects of this study and the object of this research was questions at the end of the even semester for Automotive Basic Work for class X TKRO in the 2022/2023 academic year. Question items analyzed by Anates 4.0.9, which analyzes the question items basic on validity, reliability, difficulty level index, difference level index, and distractor effectiveness, are used as the base for taking the conclusion and determining the qualities of the question items.This study shows 40 question items. There are 24 questions (60%) that fall into the very good category. Furthermore, 11 questions (27,5%) fall into the good category, 4 questions (10%) fall into the sufficient category, and 1 question (5%) fall into the bad category. Overall, the qualities of basic question items in all categories are fine.